Utilization of Electric Metal Mesh Filter for Submicron Particles Collection - Sayoud, Mohamed Akram; Zouzou, Noureddine; Zouaghi, Ayyoub (Conference record of the Industry Applications Conference, 2024)
This paper aims to explore experimentally the effects of geometric parameters on the collection efficiency of submicron particles using a developed filter assembly. The studied parameters include mesh size and fiber diameter of a metallic grid, as well as the number of the grids and the spacing between them. Results indicate that filtration efficiency can be significantly enhanced by reducing mesh size, fiber diameter, and grid spacing. Furthermore, adding more layers of grids can also improve the filter's performance. This investigation highlights the complex relationship between geometric parameters and the filtration efficiency, offering key insights essential for optimizing filter's design and effectiveness.